RETRACTED ARTICLE: TRIM11 overexpression promotes proliferation, migration and invasion of lung cancer cells - Xiaolin Wang; Weiping Shi; Hongcan Shi; Shichun Lu; Kang Wang; Chao Sun; Jiansheng He; Weiguo Jin; Xiaoxia Lv; Hui Zou; Yusheng Shu (Journal of Experimental & Clinical Cancer Research, 2016)
Abstract Background Tripartite Motif Containing 11 (TRIM11), a member of TRIM proteins, is overexpressed in high-grade gliomas and plays an oncogenic function in glioma biology. However, little is known about the role of TRIM11 in lung cancer. Methods We analyzed TRIM11 mRNA expression in lung cancer tissues and adjacent non-neoplastic tissues by real-time PCR. We then explored the function of TRIM11 in lung cancer cells by small interfering RNA-mediated downregulation of this protein followed by analyses of cell proliferation, migration and invasion. Results TRIM11 was highly expressed in lung cancer tissues and lung cancer cell lines. The higher expression of TRIM11 was correlated with the poorer prognosis of patients. Suppressing of TRIM11 expression in lung cancer cells with higher expression of TRIM11 (A549 and NCI-H446 cells) significantly reduced cell growth, motility and invasiveness. We further demonstrated that knockdown of TRIM11 affected the expression of cell proliferation-related proteins (Cyclin D1 and PCNA), and epithelial-mesenchymal transformation-related proteins (VEGF, MMP-2, MMP-9, Twist1, Snail and E-cadherin). The activity of ERK and PI3K/AKT was also suppressed in TRIM11 knocked down cells. Further experiments in lung cells with lower expression of TRIM11 (NCI-H460 and NCI-H1975 cells) with AKT inhibitor suggested that TRIM11 may promote cell motility and invasiveness through AKT pathway. Conclusions Our results indicate that TRIM11 acts as an oncogene in lung cancer through promoting cell growth, migration and invasion. Our findings may have important implication for the detection and treatment of lung cancer.